Jawi Writing in Al-Quran and Al-Sunnah Subject at Secondary School; Issues and Challenges - Kamaruzaman, Amrina Rasyada; Nik Abdullah, Nik Md. Saiful Azizi (2021)
In this research, we are studying a new phenomenon that appeared among the students of the Qur’an and Sunnah subject. It was observed that students struggle with the Jawi script, which disrupts the process of learning and teaching. Teachers had to find a solution for that obstacle, instead of using the Jawi script, they used the Rumi script in Islamic Education subject. Based on the analysis of SPM Trial Examination for the Quran and Sunnah subjects -according to the three schools that took this subject, a total of 20 students failed the exam. There was a big controversy about why the problem was in the Jawi script. Interestingly, the researchers observed that the Jawi script is less used and less cared about in schools, we can say it is limited only in teaching it formally in primary school through the J-Qaf program, while in secondary school, it is only included in the subject of Islamic Education.A. Research (Dirāsah)